Valorization of spent coffee ground and coffee silverskin as a source of nutrients and bioactive compounds - Agnese Santanatoglia; Laura Alessandroni; Cinzia Mannozzi; Riccardo Marconi; Diletta Piatti; Gianni Sagratini; Sauro Vittori; Giovanni Caprioli (Future Postharvest and Food)
Abstract In a world where a greener approach is increasingly necessary, it is mandatory to reduce waste production and reuse residues from the company's supply chain. Spent Coffee grounds (SCG) and Coffee Silverskin (CS) are two important by‐products of coffee production, being sources of important dietary fibers and bioactive compounds, which is why some authors have proposed their reuse in the nutraceutical, food and cosmetic industries. However, their nutrients chemical content has been insufficiently studied. Therefore, the aim of the present review was to investigate the main components, such as carbohydrates, dietary fibers, lipids, and bioactive compounds of SCG and CS. In addition, the most common extraction methods to obtain these aforementioned nutrients were evaluated.